2013
DOI: 10.4103/0019-5049.108559
|View full text |Cite
|
Sign up to set email alerts
|

Target-controlled infusion (Propofol) versus inhaled anaesthetic (Sevoflurane) in patients undergoing shoulder arthroscopic surgery

Abstract: Background:One of the challenges of anaesthesia for shoulder arthroscopic procedures is the need for controlled hypotension to lessen intra-articular haemorrhage and thereby provide adequate visualisation to the surgeon. Achievement of optimal conditions necessitates several interventions and manipulations by the anaesthesiologist and the surgeon, most of which directly or indirectly involve maintaining intra-operative blood pressure (BP) control.Aim:This study aimed to compare the efficacy and convenience of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
6
1
Order By: Relevance
“…A few previous studies did focus on comparing haemodynamic effects of different anaesthetic agents, but in the LDP. [ 11 12 ] In contrast to previous findings, we observed equivalent SBPs, MBPs, and HR mean s with both agents in BCP arthroscopy. While rejecting the null hypothesis, we also checked whether sevoflurane could achieve haemodynamic status equivalent with isoflurane.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A few previous studies did focus on comparing haemodynamic effects of different anaesthetic agents, but in the LDP. [ 11 12 ] In contrast to previous findings, we observed equivalent SBPs, MBPs, and HR mean s with both agents in BCP arthroscopy. While rejecting the null hypothesis, we also checked whether sevoflurane could achieve haemodynamic status equivalent with isoflurane.…”
Section: Discussioncontrasting
confidence: 99%
“…Our previous study on shoulder arthroscopy in lateral decubitus position (LDP) demonstrated approximately 10 mmHg mean difference of SBP between group subjects when different techniques and inhalational agents were compared. [ 11 12 ] Based on this, we calculated the sample size for this study. A minimum of 16 patients were required in each group to detect a mean BP difference of 10 mmHg [power 80%, α = 0.05, with standard deviation (SD) of 10 in each group] assuming that differences of <10 mmHg would not be clinically significant.…”
Section: Methodsmentioning
confidence: 99%
“…While comparison of the efficacy of isoflurane vis-a-vis sevoflurane in hypotensive anaesthesia for shoulder arthroscopy formed the primary objective of our study, a new analytical approach, process capability indices (PCIs), different from conventional statistical methodologies deriving significance from P values[78910] was additionally deployed to derive more practical and meaningful conclusions. For various reasons (refer Flow chart), we felt that comparisons using conventional P values could highlight some but not all significant variations, and this could ultimately result in a divergence between ‘statistical’ significance and ‘clinical’ significance.…”
Section: Discussionmentioning
confidence: 99%
“…Third, evaluations of experimental factors such as pain scores were not performed blindly after the assignment of patients into the three groups. Since it is known that factors associated with incisions such as fibrosis and joint inflammation influence the operation time and types of anesthetics [ 29 ], future research will be required to study those factors.…”
Section: Discussionmentioning
confidence: 99%